Five percent CO2 inhalation alleviates hippocampal glutamate and water homeostasis disturbance, neuronal damage, and learning‐memory impairment in sleep‐deprived rats - Zhihong Zhao; Xiaojun Zhang; Xiaolei Zhang; Shiyan Xie; Yue Chen; Lingfeng Lai; Lijing Xin; Jitian Guan; Yan Lin; Renhua Wu (Neuroprotection, 2024)
Abstract Background Sleep deprivation causes hippocampal injury, manifesting as neuronal damage and learning‐memory impairment. These negative effects may be associated with disturbance of hippocampal glutamate and water homeostasis, which induces excessive neuronal excitability. Five percent CO2 inhalation has been shown to suppress neuronal excitability. Here, we aimed to investigate whether 5% CO2 inhalation facilitates the recovery of hippocampal glutamate and water homeostasis, neuron morphology, and learning‐memory ability in sleep‐deprived rats. Methods Thirty‐six Sprague‐Dawley female rats were randomly divided into three groups including normal sleep (Group 1, NS, n = 12), sleep deprivation followed by sleep recovery (Group 2, SD+SR, n = 12), sleep deprivation followed by sleep recovery and 5% CO2 inhalation (Group 3, SD+SR+CO2, n = 12) by random number table. Each group was divided into two subgroups (n = 6 each subgroup) for different experiments randomly by random number table. Results We found that 5% CO2 inhalation facilitated the recovery of hippocampal glutamate concentration (7.549 ± 0.310, 8.716 ± 0.463, and 7.493 ± 0.281 mmol/L at Days 1, 3, and 5 in Group 3, F2, 15 = 22.06, p < 0.0001) and hippocampal apparent diffusion coefficient mean value (8.210 ± 0.274, 7.685 ± 0.171, 8.265 ± 0.269 at Days 1, 3, and 5 in Group 3, F2, 15 = 10.45, p = 0.0014), enhanced expression level of astrocyte‐specific membrane protein glutamate transporter‐1, promoted the polarized distribution of aquaporin 4, reduced hippocampal neuronal damage and improved learning‐memory ability in sleep‐deprived rats. Conclusion This study showed that 5% CO2 inhalation can serve as a novel strategy for alleviating sleep deprivation‐induced hippocampal injury.